The Impacts of Socio-Cultural Practices on Female Studentsa College Education in Oromia: The Case of Jimma College of Teachers Education (Global Journal of Human-Social Science, 2016)
The general purpose of this study was to identify some socio-cultural factors that affect female students College education and then to indicate intercultural educational issues in line with young female students College education in Oromia by taking JCTE as the case study area The study was a mixed approach investigation which involves index of qualitative variation that measure the dispersion of quantitative way that are available at nominal level variable through triangulating with qualitative inquires The investigation of this qualitative approach was using purposive sampling through which case studies personal observation FGD and semi-structured interview was employed The information gathered was organized and analyzed using tabulations showing both percentages and index of quantitative variations The quotation of field narrations were also included The result indicated that the major barriers to female students college education in classroom participation of formal education were both the cultural and traditional values and their prospects for educational opportunities Traditional beliefs practices and proverbs perpetuate gender imbalance in terms of educational achievements and classroom performance The study also found the factors that negatively affect female students education in JCTE in emphasizing to pregnancy lack of female models low level parental education and negative parental attitudes towards female students education from their very growing up low value attached to education and sexual harassments by their classmates and male teachers To ameliorate the existing situation the study suggested in a way of conclusion about the use of culture procedures for teacher training and applications of cultural information to curriculum Therefore it was also suggested that a serious consideration in educational teacher training that could be given on the following areas Knowing the effects of cultural and socioeconomic var